Effects of early or late prenatal immune activation in mice on behavioral and neuroanatomical abnormalities relevant to schizophrenia in the adulthood. Issue 58 (22nd January 2017) - da Silveira, Vivian T.; de Castro Medeiros, Daniel; Ropke, Jivago; Guidine, Patricia A.; Rezende, Gustavo H.; Moraes, Marcio Flavio D.; Mendes, Eduardo Mazoni A.M.; Macedo, Danielle; Moreira, Fabricio A.; de Oliveira, Antonio Carlos P.
Abstract: Maternal immune activation (MIA) during pregnancy in rodents increases the risk of the offspring to develop schizophrenia‐related behaviors, suggesting a relationship between the immune system and the brain development. Here we tested the hypothesis that MIA induced by the viral mimetic polyinosinic‐polycytidylic acid (poly I:C) in early or late gestation of mice leads to behavioral and neuroanatomical disorders in the adulthood. On gestational days (GDs) 9 or 17 pregnant dams were treated with poly I:C or saline via intravenous route and the offspring behaviors were measured during adulthood. Considering the progressive structural neuroanatomical alterations in the brain of individuals with schizophrenia, we used magnetic resonance imaging (MRI) to perform brain morphometric analysis of the offspring aged one year. MIA on GD9 or GD17 led to increased basal locomotor activity, enhanced motor responses to ketamine, a psychotomimetic drug, and reduced time spent in the center of the arena, suggesting an increased anxiety‐like behavior. In addition, MIA on GD17 reduced glucose preference in the offspring. None of the treatments altered the relative volume of the lateral ventricles. However, a decrease in brain volume, especially for posterior structures, was observed for one‐year‐old animals treated with poly I:C compared with control groups. Thus, activation of the maternal immune system at different GDs lead to neuroanatomical and behavioral alterations possibly related to the positive and negative symptoms of schizophrenia. These results provide insights on neuroimmunonological and neurodevelopmental aspects of certain psychopathologies, such as schizophrenia.